Mechanical and Fractographical Characterization of Extruded Al-Mg-Si-Zr Alloys - Kahrıman Fulya; Zeren Muzaffer (MATEC Web of Conferences, 2018)
In this study, the chemical composition of Al-0.8Mg-0.8Si alloys was modified with the addition of 0.1 and 0.2 wt.-% Zr. The billets were manufactured by direct chill casting method, homogenized at 560 °C for 6h and then extruded in order to obtain profiles having hollow and circular sections. Recrystallization layer (shell) became narrower due to the addition of Zr. This was attributed to the formation of very fine precipitates (Al3Zr) within the matrix. The mechanical properties showed that both yield and tensile strengths increased as a function of Zr content. Tensile fracture surfaces were examined by scanning electron microscope and the fractographs reflected the effect of grain structure on the fracture behavior of studied alloys. All fracture surfaces indicated typical dimple ruptures, however, the size of dimples were observed as finer structures as a function of Zr content. As seen in cross-sectional graphs, as the Zr content increased the grain structure was refined due to Al3Zr precipitates. These fine precipitates caused the formation of fine and shallow dimples under loading.